2020
DOI: 10.1002/ece3.6606
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of breeding plumages in birds: A multiple‐step pathway to seasonal dichromatism in New World warblers (Aves: Parulidae)

Abstract: Many species of birds show distinctive seasonal breeding and nonbreeding plumages. A number of hypotheses have been proposed for the evolution of this seasonal dichromatism, specifically related to the idea that birds may experience variable levels of sexual selection relative to natural selection throughout the year. However, these hypotheses have not addressed the selective forces that have shaped molt, the underlying mechanism of plumage change. Here, we examined relationships between life‐history variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 96 publications
5
35
0
Order By: Relevance
“…Data from the Macaulay Library image collection can also supplement other data sets to help answer questions related to molt intensity and duration (Rohwer et al 2009) and to the evolution of preformative molts and formative plumages through phylogenetic comparative or ancestral state reconstruction analysis (cf. Kiat et al 2019), as have recently been performed based on specimens in other New World bird families such as Cardinalidae (Guallar et al 2020) and Parulidae (Terrill et al 2020). To best further such research, finally, I encourage those contributing images to eBird to include birds in molt or in worn plumages, even if they may not be as appealing as, for example, adult males in definitive plumage, of which >50% of hummingbird images I examined referred.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Macaulay Library image collection can also supplement other data sets to help answer questions related to molt intensity and duration (Rohwer et al 2009) and to the evolution of preformative molts and formative plumages through phylogenetic comparative or ancestral state reconstruction analysis (cf. Kiat et al 2019), as have recently been performed based on specimens in other New World bird families such as Cardinalidae (Guallar et al 2020) and Parulidae (Terrill et al 2020). To best further such research, finally, I encourage those contributing images to eBird to include birds in molt or in worn plumages, even if they may not be as appealing as, for example, adult males in definitive plumage, of which >50% of hummingbird images I examined referred.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses are important for the study of evolutionary processes to correct for the nonindependence among species (Ives & Zhu, 2006), but they have not been used to look at the evolution of winter molt strategies in passerines. In a recent study of the Nearctic-Neotropical Family Parulidae, Terrill et al (2020) concluded that structural needs driven by feather damage during the annual cycle drive the evolution of prealternate molts. However, the extent to which this is the case across the diverse molt strategies of passerines as a whole remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although phylogenetic analyses have not been conducted yet to study winter molts in all Passeriformes, potential drivers of the evolution of the prebasic molt on the overwintering grounds have been hypothesized (but see Svensson & Hedenström, 1999;Terrill et al, 2020 for studies on particular families). Barta et al (2008) created models that linked winter molt in migratory birds with food seasonality; lack of resources at the end of the summer combined with an abundance of resources on the overwintering grounds during winter could have led to the evolution of winter molt (see also Remisiewicz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, seasonal plumages are thought to reflect differential selection on feather function throughout the year, but recent studies have focused on the evolution of biannual molts and seasonal phenotype change have found evidence for more complicated scenarios. In the New World warblers (Parulidae), Terrill et al (2020) found that the evolution of biannual molt appears to be linked to long-distance migration, and hypothesized that feather wear plays a primary role in the evolution of a biannual molt.…”
Section: Molt: Change Of Functionmentioning
confidence: 99%
“…This is in contrast to other studies (Hawkins et al 2012, Lyon and Montgomerie 1986, McDonald 1993, Studd and Roberston 1985 that propose adaptive mechanisms for delayed plumage maturation based on social interactions on the breeding grounds. These hypotheses are backed by substantial theory, but as with the evolution of seasonal plumage change (Terrill et al 2020), the story appears to be more complicated when molt is considered. New research into delayed plumage maturation with high-quality spectral analysis has since found further evidence that selection away from breeding sites affects plumage maturation, even in highly social birds like the manakins (Pipridae) (Morales-Betancourt and Castano-Villa 2018).…”
Section: Molt: Change Of Functionmentioning
confidence: 99%